2021
DOI: 10.1111/ejss.13116
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil respiration (Rs) and its controls are subjected to strong seasonality in an even‐aged European beech (Fagus sylvatica L.) stand

Abstract: Uncertainties arising from the so‐far poorly explained spatial variability of soil respiration (Rs) remain large. This is partly due to the limited understanding about how spatially variable Rs actually is, but also on how environmental controls determine Rs's spatial variability and how these controls vary in time (e.g., seasonally). Our study was designed to look more deeply into the complexity of Rs's spatial variability in a European beech even‐aged stand, covering both phenologically and climatically cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
3
6
0
Order By: Relevance
“…Mean SR fluxes at our forest sites are within the same order of magnitude as those measured at a 15‐year‐old spruce forest in Ireland, a temperate mixed forest in Germany, and a beech forest in Romania (Saiz et al., 2006; Oertel et al., 2015; Hereș et al., 2021; Table S5 in Supporting Information ). Our forest fluxes are also comparable with those reported from a pine forest in Canada (Peichl et al., 2010).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Mean SR fluxes at our forest sites are within the same order of magnitude as those measured at a 15‐year‐old spruce forest in Ireland, a temperate mixed forest in Germany, and a beech forest in Romania (Saiz et al., 2006; Oertel et al., 2015; Hereș et al., 2021; Table S5 in Supporting Information ). Our forest fluxes are also comparable with those reported from a pine forest in Canada (Peichl et al., 2010).…”
Section: Discussionsupporting
confidence: 68%
“…As a result, so far, most studies on the spatial‐variability of soil GHG fluxes have been conducted at a laboratory scale through incubation measurements under standardized conditions (e.g., Arias‐Navarro et al., 2017; Mathieu et al., 2006). However, few studies have evaluated this through direct field measurements, though these studies usually focus on well‐defined field plots of sizes <1 ha (e.g., Flessa et al., 1995; Hereș et al., 2020; Nkongolo et al., 2010). These obvious short‐comes call for a more comprehensive field‐based sampling approach that explores the importance of heterogeneities of landscape features and soil conditions on the small‐scale variability of GHG fluxes within landscapes in order to better constrain the controlling environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Mean SR fluxes at our forest sites are within the same order of magnitude as those measured at a 15-year-old spruce forest in Ireland, a temperate mixed forest in Germany, and a beech forest in Romania (Saiz et al, 2006;Oertel et al, 2015;Hereș et al, 2021; Table S5 in Supporting Information S1). Our forest fluxes are also comparable with those reported from a pine forest in Canada (Peichl et al, 2010).…”
Section: Forest (Soil Respiration)supporting
confidence: 62%
“…Moreover, to avoid potential CO 2 leaks due to the shallow insertion of the soil respiration chamber, the chamber was strongly pressed against the soil during the entire time that measurements were performed. Some studies have shown a strong correlation between insertion depth, the number of cut roots, and the lost soil effluxes (Silvola et al, 1996; Wang et al, 2005), therefore, no collars were inserted into the soil (Epron et al, 2004; Hereș et al, 2021; Poblador et al, 2017). R s values were estimated for 120 s based on the linear increase of the CO 2 concentration within the soil respiration chamber (i.e., a closed dynamic system).…”
Section: Methodsmentioning
confidence: 99%